Evaluation of the effectiveness of some essential oils against zoonotic methicillinresistant Staphylococcus aureus isolated from dairy products and humans - Salman, Marwa B; Abdelaziz Zin Eldin, Asmaa Ibrahim; Eissa, Nourhan; Maher, Ahmed; Aish, Abd Elghany; El Moez, Sherein I Abd (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: Staphylococcus aureus (S. aureus) is a zooanthroponotic, nosocomial, and community- associated pathogen that threatens livestock management and even public health. The goal of this investigation was to clarify the role of S. aureus in zoonotic illnesses. Besides that, a novel trial was conducted in the current Egyptian study using oil extracts such as cactus oil, tea oil, geranium oil, and thyme oil to demonstrate the susceptibility of methicillin-resistant S. aureus (MRSA) isolates to these organic oils in response to the alarming global concern regarding the decreased susceptibility of S. aureus to known antibiotics, which exacerbates control and treatment protocols. Material and Methods: A total of 110 samples (45 raw cattle milk samples, 35 Karish cheese samples, and 30 human sputum samples) were collected. The bacterium was identified via traditional culturing methods, Gram staining, and the application of several biochemical tests. After that, various kinds of known commercial antibiotics were used to detect the antimicrobial susceptibility (AMS) of the obtained isolates. Furthermore, conventional polymerase chain reaction (PCR) testing was performed to identify S. aureus (nuc gene) and MRSA (mecA gene), with further application of multiplex PCR for screening of all the obtained isolates for vancomycin resistance via targeting vanA, vanB, and vanC genes. Finally, the agar gel diffusion method was performed to assess the antibacterial activity of four plant extracts (cactus oil, tea oil, geranium oil, and thyme oil) against the obtained MRSA. Results: The culturing method revealed S. aureus positivity in raw cattle milk (13.33%), in Karish cheese (28.57%), and in human samples (20%). The obtained isolates showed mainly resistance to amoxicillin-clavulanic and ampicillin antibiotics, while the dairy samples showed further resistance against ceptaxime and an intermediate reaction against erythromycin. On the molecular side, PCR positivity was present in human samples (10%), raw cow milk (13.33%), and Karish cheese (14.29%). Nine of the fourteen PCR isolates were methicillin-resistant S. aureus (MRSA) isolates. Comparing the four oil extracts against the acquired MRSA isolates, cactus oil extract proved to be the most effective. Conclusion: The study’s results are highly promising as they support the notion that certain essential oils possess strong antimicrobial properties against zoonotic S. aureus, thereby reducing the excessive use of antibiotics in veterinary and medical settings. Adv. Vet. Anim. Res., 11(2): 306-316, June 2024 http://doi.org/10.5455/javar.2024.k778